Understanding Students' Creative Processes in Solving Open-Ended Statistical Problems Within a Culturally Responsive Environment - Relitasari, Puput; Fashihah, Fashihah; Agustina, Vena; Ainiyah, Qurrotul (Jurnal Pendidikan Progresif, 2025)
Understanding Students' Creative Processes in Solving Open-Ended Statistical Problems Within a Culturally Responsive Environment. Objectives: This study aims to analyze the creative thinking process in solving open-ended problems through Culturally Responsive Teaching (CRT) based on personal experience using SPSS. Methods: This qualitative case study sample consisted of 26 international students from a mathematics education program. Three subjects were selected by purposive sampling to be interviewed based on flexibility, fluency, and novelty. Data were obtained through tests and interviews (triangulation methods), which were analyzed, included data collection, analysis, research findings, and interpretation based on Wallas' theory (preparation, incubation, illumination, and verification). Findings: The four stages appeared in the creative thinking process of the three subjects, but not linearly. In the preparation, the subject showed the ability to understand the problem based on a learning experience. The incubation is characterized by the exploration of strategies, both technical (A1), contextual (A2), and structural-conceptual (A3). Illumination occurs when subjects discover new connections between methods or unexpected analysis results. In the verification stage, they not only check procedures but also encourage reflection on the meaning of the data. This dynamic shows that creative thinking is cyclical and flexible. In the flexibility, three subjects showed different approaches in combining data visualization and statistical tests, with a tendency to move between stages of thinking. On the fluency, subjects were able to generate multiple problem contexts based on learning experiences, but varied in the depth of reflection and strategy used. There were original reconstructions of ideas and problem structures on the novelty, especially when facing bidirectional data, with meaningful interpretations influenced by their respective learning experiences. The CRT appeared strong in the way subjects connected statistical data with learning experiences. It allows students to strengthen the meaning at each stage of creative thinking. The findings emphasize the importance of CRT to develop contextual creative thinking. Keywords: creative thinking, culturally responsive teaching, open-ended problem, SPSS.